2020
DOI: 10.1155/2020/6432173
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Activity of Eucommia Ulmoides Oliv: Male Flower Extract in Spontaneously Hypertensive Rats

Abstract: Eucommia ulmoides Oliv. is a traditional medical plant in Asia; however, it is still unknown whether Eucommia male flowers have an antihypertensive activity. In this study, we found that the aqueous extract of Eucommia ulmoides Oliv. male flowers can lower the blood pressure of SHR in a dose-dependent manner. Mechanistic studies suggested that the aqueous extract of male flowers can promote the mRNA and protein expressions of ACE2 in the kidney of SHR. ELISA assay showed that the plasma levels of ANG II was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
(31 reference statements)
0
9
0
Order By: Relevance
“… Shi et al (2013) Osthole (natural coumarine derivative) Male Sprague-Dawley rats/ Bleomycin induced pulmonary fibrosis model Increased pulmonary ACE2 immunostaining, mRNA and protein expression in fibrotic lung group Y. Hao & Liu et al (2016) Sini decoction/ Traditional Chinese medicine Male ICR mice / E. coli induced lung injury model Increased lung ACE2 protein expression J. Liu et al (2018) Sini decoction/ Traditional Chinese medicine Male ICR mice / Lipopolysaccharide induced lung injury Increased lung ACE2 immunostaining and protein expression in injured mice Q. Chen et al (2019b) Eucommia ulmoides Oliv/ Traditional Chinese medicine Male spontaneously hypertensive and Sprague Dawley rats Increased renal ACE2 mRNA and protein expression in hypertensive rats Z. J. Ding et al (2020) Qishenyiqi / Traditional Chinese medicine Male Sprague-Dawley rats/ Coronary artery ligation induced disease model Increased cardiac ACE2 mRNA expression Y. Wang, C. Li, et al (2012) Puerarin (a natural hypertensive compound) Male Sprague Dawley/ Goldblatt hypertensive rat model No change in renal ACE2 mRNA expression in non-ischemic kidneys S. Bai et al (2013) Baicalin (flavonoid) Human umbilical vein endothelial cells/ Ang II treated cells Increased ACE2 mRNA and protein expression. X.…”
Section: Phytochemicals and Naturally Occurring Substances And Ace2mentioning
confidence: 99%
“… Shi et al (2013) Osthole (natural coumarine derivative) Male Sprague-Dawley rats/ Bleomycin induced pulmonary fibrosis model Increased pulmonary ACE2 immunostaining, mRNA and protein expression in fibrotic lung group Y. Hao & Liu et al (2016) Sini decoction/ Traditional Chinese medicine Male ICR mice / E. coli induced lung injury model Increased lung ACE2 protein expression J. Liu et al (2018) Sini decoction/ Traditional Chinese medicine Male ICR mice / Lipopolysaccharide induced lung injury Increased lung ACE2 immunostaining and protein expression in injured mice Q. Chen et al (2019b) Eucommia ulmoides Oliv/ Traditional Chinese medicine Male spontaneously hypertensive and Sprague Dawley rats Increased renal ACE2 mRNA and protein expression in hypertensive rats Z. J. Ding et al (2020) Qishenyiqi / Traditional Chinese medicine Male Sprague-Dawley rats/ Coronary artery ligation induced disease model Increased cardiac ACE2 mRNA expression Y. Wang, C. Li, et al (2012) Puerarin (a natural hypertensive compound) Male Sprague Dawley/ Goldblatt hypertensive rat model No change in renal ACE2 mRNA expression in non-ischemic kidneys S. Bai et al (2013) Baicalin (flavonoid) Human umbilical vein endothelial cells/ Ang II treated cells Increased ACE2 mRNA and protein expression. X.…”
Section: Phytochemicals and Naturally Occurring Substances And Ace2mentioning
confidence: 99%
“…Eucommia ulmoides Oliver, belonging to monotypic family Eucommiaceae, is a woody perennial dioecious plant native to China and its male flower has favorable prospects ( Ding et al, 2015 ). The male flowers of E. ulmoides are available in relatively large yields and are easy to harvest ( Ding et al, 2020 ). Moreover, E. ulmoides male flower is abundant in phytonutrients and various biologically active substances including phenols, flavonoids, chlorogenic acid, and aucubin, which possess stronger antioxidant, anti-inflammatory, antihypertensive, and analgesic effects ( Xing et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has reported that Atractylodes macrocephala and Poria cocos can enhance human immunity [ 29 , 30 ]. Uncaria rhynchophylla and Eucommia ulmoides have strong antihypertensive, sedative, spasmodic, and diuretic effects [ 31 , 32 ]. Chrysanthemum morifolium extract solution can dilate blood vessels, reduce blood pressure, and reduce the cardiac output [ 33 ].…”
Section: Discussionmentioning
confidence: 99%